Wolf presence in the ranch of origin: Impacts on temperament and physiological responses of beef cattle following a simulated wolf encounter - Cooke, R. F. [UNESP]; Bohnert, D. W.; Reis, M. M.; Cappellozza, B. I. (Amer Soc Animal Science, 2013)
This experiment evaluated temperament, vaginal temperature, and plasma cortisol in beef cows from wolf-naive and wolf-experienced origins that were subjected to a simulated wolf encounter. Multiparous, pregnant, nonlactating Angus-crossbreed cows from the Eastern Oregon Agricultural Research Center located near Burns, OR (CON; n = 50), and from a commercial operation near Council, ID (WLF; n = 50), were used. To date, grey wolves are not present around Burns, OR, and thus CON were naive to wolves. Conversely, wolves are present around Council, ID, and WLF cows were selected from a herd that had experienced multiple confirmed wolf-predation episodes from 2008 to 2012. Following a 50-d commingling and adaptation period, CON and WLF cows were ranked by temperament, BW, and BCS and allocated to 5 groups (d 0; 10 CON and 10 WLF cows/group). Groups were individually subjected to the experimental procedures on d 2 (n = 3) and d 3 (n = 2). Before the simulated wolf encounter, cow temperament was assessed and blood samples and vaginal temperatures (using intravaginal data loggers) were collected (presimulation assessments). Cows were then sorted by origin, moved to 2 adjacent drylot pens (10 WLF and 10 CON cows/pen), and subjected to a simulated wolf encounter event for 20 min, which consisted of 1) cotton plugs saturated with wolf urine attached to the drylot fence, 2) continuous reproduction of wolf howls, and 3) 3 leashed dogs that were walked along the fence perimeter. Thereafter, WLF and CON cows were commingled and returned to the handling facility for postsimulation assessments, which were conducted immediately after exposure to wolf-urine-saturated cotton plugs, wolf howl reproduction, and 20-s exposure to the 3 dogs while being restrained in a squeeze chute. Chute score, temperament score, and plasma cortisol concentration increased (P <= 0.01) from pre- to postsimulation assessment in WLF but did not change in CON cows (P >= 0.19). Exit velocity decreased (P = 0.01) from pre-to postsimulation assessment in CON but did not change (P = 0.79) in WLF cows. In addition, WLF cows had a greater (P = 0.03) increase in temperature from pre-to postsimulation assessments compared with CON cows. In conclusion, the simulated wolf encounter increased excitability and fear-related physiological stress responses in cows that originated from a wolf-experienced herd but not in cows that originated from a wolf-naive herd.
Keywords: beef cattle; physiology; stress; temperament; wolves